Educational Management and Educational Personnel At MI Negeri 2 Polanharjo Klaten - Agus Ahmad Zamroni; Purwanto Purwanto (Journal of Mandalika Social Science, 2026)
The purpose of this study was to (1) examine the management of educators and educational staff at MI Negeri 2 Polanharjo, and (2) identify the obstacles faced in the management of educators and educational staff at MI Negeri 2 Polanharjo. This study used a qualitative descriptive approach. Data were collected through interviews, observations, and documentation. Data analysis was carried out by means of data reduction, data presentation, and drawing conclusions/verification. The results of the study indicate that the management of educators and educational staff at MI Negeri 2 Klaten consists of: (1) planning of educators and educational staff submitted from the madrasah to the Regional Office of the Ministry of Religious Affairs, using three analyses: needs analysis, job analysis, and workload analysis, so that it is possible to analyze strengths and weaknesses; (2) placement of educators based on the principle of "the right man on the right place," even though there is still a mismatch between educational background and the subjects taught; (3) development activities for educators and educational staff include education and training, such as technical guidance, further studies, and self-development through religious studies and coaching.